2022
DOI: 10.3389/fsufs.2022.962268
|View full text |Cite
|
Sign up to set email alerts
|

Backyard poultry farming with improved germplasm: Sustainable food production and nutritional security in fragile ecosystem

Abstract: Approximately 3 billion people were unable to afford a healthy diet in 2019 because of poverty and inequality. Most of these people live in Asia and Africa. Furthermore, 30% of the world population was affected by moderate to severe food insecurity in 2020, and most of this population lives in low- and middle-income countries. The world is at a critical juncture, and there is an urgent need for transformative food systems that ensure the empowerment of poor and vulnerable population groups, often smallholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The percentage of indigenous chicken units owned by women was higher in sub-temperate agro-ecology. It has previously been reported that in less developed regions, indigenous chicken is generally owned and managed by women ( 7 , 17 , 23 , 24 ). In sub-temperate agro-ecology, the respondents had less education level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of indigenous chicken units owned by women was higher in sub-temperate agro-ecology. It has previously been reported that in less developed regions, indigenous chicken is generally owned and managed by women ( 7 , 17 , 23 , 24 ). In sub-temperate agro-ecology, the respondents had less education level.…”
Section: Discussionmentioning
confidence: 99%
“…Although their productivity is lower than that of intensively raised birds ( 9 ), indigenous chickens contribute to food and nutritional security, economic security, and ecological resilience ( 3 , 5 , 10 ). In Indian Himalayan Region (IHR), the indigenous chickens have been part of the indigenous food system of tribal and indigenous people for centuries ( 7 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are primarily driven by the collective impacts of demand-supply chains, urban planning, and poultry management on public health concerns (GoI, 2022; S. Kumar et al, 2017). As a result, the traditional practice of rearing poultry in sheds and backyards is being replaced by organised poultry cooperatives (GoI, 2019), which is affecting the number of country-breeds and homogenising the overall poultry germplasm (Bennett et al, 2018;Chatterjee & Rajkumar, 2015;M. Singh et al, 2022).…”
Section: Study Area and The Ecology Of Poultry Wastementioning
confidence: 99%
“…Livestock and poultry farming are practiced by the people since time immemorial and are symbolic to the health and wealth of a Naga family (Singh et al 2019a). Livestock farming plays a pivotal role in supplementing family income and generating employment (Singh et al 2022) for the rural poor apart from efficient utilization of agricultural products and byproducts not suitable for human consumption (GON 2015, Report of Task force on agriculture development).…”
mentioning
confidence: 99%